Bodies and Behaviours: A Study of Body Image in Adolescent Girls and the Canadian Church - Michaelson, Valerie (Practical theology, 2016)
This is an interdisciplinary study that applies Christian feminist theology and health sciences' insights to the results of a study concerning adolescent girls and body image. The desire of adolescent girls to be thin is inherently connected to their desire for wholeness, acceptance and unconditional love, and the promise of Christianity reaches a wholeness of this depth. And yet, the reality of the church's relationship to the female body often results in destructive patterns of low body image and emotional health. Thus, using quantitative methods, we employed a large and representative sample of Canadian adolescent girls to: (1) investigate how often they report healthy and unhealthy images of their bodies; (2) relate perceptions of body image to self-reported adiposity (body mass index or BMI) status; (3) relate perceptions of body image to diets and other measures used to control body weight; and (4) to determine whether the above perceptions and relationships are modified by participation in church or religious groups. We present an initial overview of our findings that suggest that church involvement does not protect adolescent girls from modern challenges with body image. We then go on to consider the possible relationship between these findings and contemporary theologies. Practical implications for the practice of spiritual care are also identified.